2017
DOI: 10.1002/ppul.23884
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function disparities exist and persist in Hispanic patients with cystic fibrosis: A longitudinal analysis

Abstract: Background Hispanic patients with cystic fibrosis (CF) have decreased life expectancy compared to non-Hispanic white patients. Pulmonary function is a main predictor of life expectancy in CF. Ethnic differences in pulmonary function in CF have been understudied. The objective was to compare longitudinal pulmonary function between Hispanic and non-Hispanic white patients with CF. Methods This cohort study of 15,018 6–25 years old patients in the CF Foundation Patient Registry from 2008 to 2013 compared FEV1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Despite Hispanic subjects having a lower pulmonary function that non‐Hispanic white subjects, there was no difference in the rate of decline in percent‐predicted FEV 1 by ethnicity in any geographic region. This is consistent with our prior findings on overall rate of percent‐predicted FEV 1 decline and pulmonary function differences by ethnicity …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Despite Hispanic subjects having a lower pulmonary function that non‐Hispanic white subjects, there was no difference in the rate of decline in percent‐predicted FEV 1 by ethnicity in any geographic region. This is consistent with our prior findings on overall rate of percent‐predicted FEV 1 decline and pulmonary function differences by ethnicity …”
Section: Discussionsupporting
confidence: 93%
“…In the largest database of Hispanic patients with CF, we found that pulmonary function disparities between Hispanic and non‐Hispanic white subjects vary among geographic regions, even with adjustment for factors known to influence pulmonary function. In all geographic regions, the difference in percent‐predicted FEV 1 between Hispanic and non‐Hispanic white subjects varied from the overall ethnic disparity of 5.8% in percent‐predicted FEV 1 that we had found in our previous work . The ethnic gap in pulmonary function was significantly wider in the West than in the other geographic regions for all measures (percent‐predicted FVC, FEV 1 , FEV 1 /FVC, FEF 25%‐75% ).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations